Le elezioni comunali del 2014 a Livorno: l'inattesa vittoria del Movimento Cinque Stelle nella roccaforte del centrosinistra - Maurizio Ribechini (QOE-IJES, 2015)
The local elections that were held in spring 2014 led to the renewal of the Municipal Councils and Mayors of over 4,000 Italian cities. The electoral results were hardly predictable by the political analysts. This is particularly true in the case of the Tuscan town of Livorno, where for the first time in history, the centre-left coalition had lost the political leadership of the city, after having governed for almost seventy years after the end of the World War II. In Livorno the mayoral candidate of the Democratic Party has been defeated after the second round by the candidate of the Five Star Movement. This article tries to shed lights on the reasons behind this political change. More specifically, the article looks at the electoral results of 2014, 2009 and 2004; moreover, it is based on interviews to politicians and observers. Finally, the article tries to provide some conclusive remarks.